Detection of the stroboscopic effect by young adults varying in sensitivity - Veitch, JA; Martinsons, C (Lighting research & technology (London, England : 2001), 2020)
The advent of LED lighting has renewed concern about the possible visual, neurobiological, and performance and cognition effects of cyclic variations in lighting system luminous flux (temporal light modulation). The stroboscopic visibility measure (SVM) characterises the temporal light modulation signal to predict the visibility of the stroboscopic effect, one of the visual perception effects of temporal light modulation. A SVM of 1 means that the average person would detect the phenomenon 50% of the time. There is little published data describing the population sensitivity to the stroboscopic effect in relation to the SVM, and none focusing on people subject to visual stress. This experiment, conducted in parallel in Canada and France, examined stroboscopic detection for horizontal and vertical moving targets when viewed under commercially available lamps varying in SVM conditions (SVM: ∼0; ∼0.4; ∼0.9; ∼1.4; ∼3.0). As expected, stroboscopic detection scores increased with increasing SVM. For the horizontal task, average scores were lower than the expected 4/8 at ∼0.90, but increased non-linearly with higher SVMs. Stroboscopic detection scores did not differ between people low and high in pattern glare sensitivity, but people in the high-pattern glare sensitivity group reported greater annoyance in the SVM ∼1.4 and ∼3.0 conditions.